Correction: Zvidzayi et al. A Novel Approach to Assess the Potency of Topical Corticosteroids. Pharmaceutics 2021, 13, 1456 - Michael Zvidzayi; Seeprarani Rath; Charles Bon; Sagaran Abboo; Isadore Kanfer (MDPI AG, 2022)
In the original publication [...]